Interpretation difficulty of normal versus abnormal radiographs using a pediatric example - Boutis, Kathy; Cano, Stefan; Pecaric, Martin; Welch-Horan, T. Bram; Lampl, Brooke; Ruzal-Shapiro, Carrie; Pusic, Martin (Canadian Medical Education Journal, 2016)
Background: Radiograph teaching files are usually dominated by abnormal cases, implying that normal radiographs are easier to interpret. Our main objective was to compare the interpretation difficulty of normal versus abnormal radiographs of a set of common pediatric radiographs. Methods: We developed a 234-item digital case bank of pediatric ankle radiographs, recruited a convenience sample of participants, and presented the cases to each participant who then classified the cases as normal or abnormal. We determined and contrasted the interpretation difficulty of the normal and abnormal x-rays items using Rasch Measurement Theory. We also identified case features that were associated with item difficulty. Results: 139 participants (86 medical students, 7 residents, 29 fellows, 5 emergency physicians, and 3 radiologists) rated a minimum of 50 cases each, which resulted in 16,535 total ratings. Abnormal cases were more difficult (+0.99 logits) than were normal ones (-0.58 logits), difference 1.57 logits (95% CI 1.2, 2.0), but there was considerable overlap in difficulty scores. Patient variables associated with a more difficult normal radiograph included younger patient age (β = -0.16, 95% CI -0.22, -0.10), history of distal fibular tenderness (β = 0.55, 95% CI 0.17, 0.93), and presence of a secondary ossification centre (β = 0.84, 95% CI 0.27, 1.41). Conclusions: While abnormal images were more difficult to interpret, normal images did show a range of interpretation difficulties. Including a significant proportion of normal cases may be of benefit to learners.